2021
DOI: 10.3389/fphar.2021.697643
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Alleviates Renal Injury in Mouse Model of Sepsis

Abstract: Melatonin (N-acetyl-5-methoxytryptamine; MLT) has been shown to have a renal-protective effect against kidney injury. However, the mechanisms underlying the protective role of MLT in sepsis-induced renal injury are yet to be revealed. In this study, MLT alleviated renal dysfunction with the increase of BUN (blood urea nitrogen) and SCR (serum creatinine) and reduction of fibrosis in the CLP (cecal ligation puncture) model. RNA-seq analysis showed that MLT repressed the oxidant stress in response to kidney inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As revealed by prior investigations, excessive ROS-induced oxidative stress may result in chronic inflammation [4][5][6], which is an important characteristic of inflammatory response as well as a crucial factor for tissue and organ fibrosis [7,8]. As an antioxidant and anti-inflammatory substance, Rg1 can inhibit the ROS level in LPS-induced cardiomyocytes [22].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As revealed by prior investigations, excessive ROS-induced oxidative stress may result in chronic inflammation [4][5][6], which is an important characteristic of inflammatory response as well as a crucial factor for tissue and organ fibrosis [7,8]. As an antioxidant and anti-inflammatory substance, Rg1 can inhibit the ROS level in LPS-induced cardiomyocytes [22].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that chronic inflammation can cause the accumulation of reactive oxygen species (ROS) [4][5][6], which is an important characteristic of the inflammatory response as well as a crucial contributor to tissue and organ fibrosis [7,8]. According to prior research, mitochondrial oxidative stress is a trigger to activate NOD-like receptor protein 3 inflammasome (NLRP3) [9], which induces various organ pathological fibrosis, including hepatic [10], renal [11], and cardiac [12].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative status consequently was changed during excessive inflammation caused by acute injury (24). We first investigated the level of ROS and found significant upregulation of ROS in the pulmonary section after ALI, which was restrained by BBR treatment (Figure 2A).…”
Section: Berberine Eliminates Excessive Inflammation In Alimentioning
confidence: 99%
“…Toon et al found that melatonin is a promising drug for the treatment of a chronic kidney disease (CKD) patient with renal fibrosis; melatonin could recover mitochondrial function by upregulating the miR-4516 expression to decrease ROS formation ( Yoon et al, 2020 ). In response to acute kidney injury induced by sepsis, melatonin could reduce the oxidative stress response and ROS accumulation of ROS in vitro and attenuate the inflammatory response by downregulating the mRNA expressions of IL-1α, IL-1β, Mcp-1 and TGF-β1, thereby proving the therapeutic effect of melatonin on acute kidney injury ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%